The influence of trust, satisfaction, value, and brand image on loyalty - Gandadinata Thamrin; Innocentius Bernarto; Yukichika Kawata (BISMA (Bisnis dan Manajemen), 2020)
This study aims to investigate the influence of trust, satisfaction, values, and brand image on the loyalty of MaxxCoffee. Data collection in this study was conducted using a questionnaire given to students of Universitas Pelita Harapan as respondents. The research design uses convenience sampling with a total sample of 249 samples. The data collection method is utilizing questionnaires and the data is analyzed by the Partial Least Square of Structural Equation Modeling (PLS-SEM). The findings of this study are trust, satisfaction, and value have a positive effect on loyalty. Conversely, the brand image has no positive effect on Maxx Coffee customers loyalty. The contribution of this study is providing input to the management of Maxx Coffee to concern and maintain their trust, satisfaction, value, and brand image of Maxx Coffee to maintain the customers loyalty.